Hong Kong on the move: 10 years as the HKSAR - MCGIFFERT, Carola (Institutional Knowledge at Singapore Management University, 2008)
The 1997 transfer of sovereignty over Hong Kong from British colonial rule to a Special Administrative Region (SAR) under the People's Republic of China captured America's worried attention. Yet more than 10 years after the handover, and despite real challenges to its economic, political, and security systems, Hong Kong has retained its vibrancy and openness based on the rule of law and a free and competitive economy. There is no question that during this period Hong Kong has been challenged. Economically, it has faced a currency crisis, a real estate bubble that burst, and a deep recession. Politically, democracy activists have accused the government of dragging its feet in pushing for universal suffrage as promised by China and Britain and enshrined in the Basic Law, Hong Kong's mini-constitution. It survived major public health threats, including an avian flu outbreak and the deadly devastation of the SARS virus. And its port, one of the largest and busiest in the world, has had to deal with the challenges of transportation security in the face of global terrorism. Instead of buckling under the pressure of these crises, Hong Kong has proven its resilience, adaptability, and creativity. Today, Hong Kong remains an open and pluralistic society, with an effective and pragmatic government, a respected and independent legal system, a free press, and a politically active populace. Many in the United States focus elsewhere only when those places have problems, not when they are doing well. But Hong Kong s achievements should be examined and celebrated. To be sure, Hong Kong will face challenges and even crises in the future. Yet the lessons of the past decade will serve it well. This volume tells Hong Kong s success story from the viewpoints of noted U.S. and Hong Kong scholars, economists, trade officials, and security experts. It offers provocative perspectives on Hong Kong's complicated political and economic development, changing identity, and complex relationship with the rest of China, as well as insights into what lies ahead for this vibrant city in an era of globalization.